DIGITALIZATION AS THE MAIN FACTOR OF HOSPITALITY INDUSTRY DEVELOPMENT IN THE CONDITIONS OF MODERN CHALLENGES - Kyryliuk , I. M.; Neshchadym , L. M.; Blahopoluchna, A.G. (The actual problems of regional economy development, 2022)
The purpose of the article is to identify features and methods of implementation and use of elements of digitalization. This will increase the efficiency of the hospitality industry in a competitive environment. During the research we used dialectical and abstract-logical methods, methods of systematic approach, comparison, observation, analysis, synthesis, induction, deduction, etc. This article explores the importance and role of digitalization in modern conditions of information society development, which forms a digital, virtual reality with specific social, cultural, consumer practices. It has been proven that the use of innovation processes and the introduction of digitalization elements in the activities of the hospitality industry significantly contribute to improving its efficiency and customer satisfaction in today's challenges. We have identified a set of circumstances that indicate the need to use Internet technologies to successfully promote the services of the hospitality industry in the market. The article analyzes the positive and negative impact of digitalization processes on the development of the hospitality industry, whose activities are aimed at meeting a variety of both individual and collective needs of consumers. We have proved that in modern conditions the Internet is an important tool for successful business development, as there are clear trends in the number of Internet users and the share of Internet commerce in total world trade. The article substantiates that the digitalization of the processes of organization of facilities, management and customer service of the hospitality industry will contribute to the formation of a single information space and increase the competitiveness of the industry. We determined that overcoming the existing negative trends in the hospitality industry, which were formed under the influence of destructive factors, will be possible with the active use of innovation, among which special attention should be paid to digital technologies and information positioning of the hospitality industry in cyberspace.